A collagen cardiac patch incorporating alginate microparticles permits the controlled release of hepatocyte growth factor and insulin‐like growth factor‐1 to enhance cardiac stem cell migration and proliferation. (19th June 2017) - O'Neill, Hugh S.; O'Sullivan, Janice; Porteous, Niamh; Ruiz‐Hernandez, Eduardo; Kelly, Helena M.; O'Brien, Fergal J.; Duffy, Garry P.
Abstract: Cardiac stem cells (CSCs) represent a logical cell type to exploit as a regenerative treatment option for tissue damage accrued as a result of a myocardial infarction. However, the isolation and expansion of CSCs prior to cell transplantation is time consuming, costly and invasive, and the reliability of cell expansion may also prove to be a major obstacle in the clinical application of CSC‐based transplantation therapy after a myocardial infarction. In order to overcome this, we propose the incorporation of growth factor‐eluting alginate microparticles into collagen‐based scaffolds as an implantable biomaterial to promote the recruitment and expansion of CSCs in the myocardium. In order to obtain scaffolds able to enhance the motogenic and proliferative potential of CSCs, the aim of this work was to achieve a sustained delivery of both hepatocyte growth factor and insulin‐like growth factor‐1. Both proteins were initially encapsulated in alginate microparticles by spray drying and subsequently incorporated into a collagen scaffold. Microparticles were seen to homogeneously distribute through the interconnected scaffold pore structure. The resulting scaffolds were capable of extending the release of both proteins up to 15 days, a three‐fold increase over non‐encapsulated proteins embedded in the scaffolds. In vitro assays with isolated CSCs demonstrated that the sustained release of both bioactive proteins resulted in an increased motogenic and proliferative effect. As presently practiced, the isolation and expansion of CSCs for autologous cell transplantation is slow, expensive and difficult to attain. Thus, there is a need for strategies to specifically activate in situ the intrinsic cardiac regenerative potential represented by the CSCs using combinations of growth factors obviating the need for cell transplantation. By favouring the natural regenerative capability of CSCs, it is hypothesized that the cardiac patch presented here will result in positive therapeutic outcomes in MI and heart failure patients in the future. Copyright © 2016 John Wiley & Sons, Ltd.